Pengaruh Kemudahan Penggunaan ERP-SAP Terhadap Kinerja Karyawan Dengan Integritas Karyawan Sebagai Variabel Moderasi - Novitasari, Hilda; Syarifuddin, Syarifuddin; Indrijawati, Aini (Universitas Logistik dan Bisnis Internasional, 2024)
This study aims to examine and analyze the effect of the ease of using Enterprise Resource Planning (ERP) based on System Application and Product (SAP) on employee performance with employees integrity as a moderating variable. The population in this research is all employees who use ERP-SAP at PT ASDP Indonesia Ferry (Persero) Region III and Region IV. This research uses a non-probability sampling method with saturation sampling (census) selection technique. Data was collected using a questionnaire to 108 employees and analyzed using Structural Equation Modeling (SEM) and Moderate Regression Analysis (MRA) using Amos 24. The results of this study indicate that ease of use of ERP-SAP has a positive and significant effect on employee performance. Employee integrity has a positive and significant effect on employee performance directly but is unable to moderate the influence of ease of use of ERP-SAP on employee performance.The conclusion obtained is that employees perceptions of the ease of use of the system have an influence on increasing their performance and humans (individuals) are unable to intervene the system to increase their performance. Goal Setting Theory is only able to explain the effect between integrity on increasing employees performance directly